Lateness - Eisenman, Peter, 1932-; Iturbe, Elisa (Point (Princeton, N.J.), 2020)
"Conceptions of modernity in architecture are often expressed in the idea of the zeitgeist, or "spirit of the age," an attitude toward architectural form that is embedded in a belief in progressive time. 'Lateness' explores how architecture can work against these linear currents in startling and compelling ways. In this incisive book, internationally renowned architect Peter Eisenman, with Elisa Iturbe, proposes a different perspective on form and time in architecture, one that circumvents the temporal constraints on style that require it to be "of the times" - lateness. He focuses on three twentieth-century architects who exhibited the qualities of lateness in their designs : Adolf Loos, Aldo Rossi, and John Hejduk. Drawing on the critical theory of Theodor Adorno and his study of Beethoven's final works, Eisenman shows how the architecture of these canonical figures was temporally out of sync with conventions and expectations, and how lateness can serve as a form of release from the restraints of the moment. Bringing together architecture, music, and philosophy, and drawing on illuminating examples from the Renaissance and Baroque periods, 'Lateness' demonstrates how today's architecture can use the concept of lateness to break free of stylistic limitations, expand architecture's critical capacity, and provide a new mode of analysis."--taken from back cover.